Pengaruh Ukuran Perusahaan, Leverage, Komisaris Independen dan Konsentrasi Kepemilikan terhadap Pengungkapan Modal Intelektual (Studi Empiris Pada Perusahaan Sektor Keuangan Yang Listing di BEI Tahun 2016-2017) - Lingsir India Anteng Tunggil Putri; Bima Cinintya Pratama (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2020)
The purpose of this study was to determine the effect of firm size, leverage, independent commissioners and ownership concentration on intellectual capital disclosure. Population in this study were financial firms listed in Indonesia Stock Exchange during 2016-2017 periods. Purposive sampling technique was used and obtained 170 samples of companies that met the criteria. Data were analyzed using multiple linier regression analysis by SPSS program. The results of this study showed firm size, leverage, independent commissioners and ownership concentration have simultaneously positive effect on intellectual capital disclosure. As partial, firm size have a positive effect on intellectual capital disclosure while, leverage, independent commissioners and ownership concentration have no effects on intellectual capital disclosure.